Liver Fibrosis Scores and Clinical Outcomes in Patients With COVID-19 - Zhang, Jing; Liu, Fuwei; Song, Tiangang; Li, Zhangwang; Xia, Panpan; Tang, Xiaoyi; Xu, Minxuan; Shen, Yunfeng; Ma, Jianyong; Liu, Xiao; Yu, Peng (Frontiers in Medicine, 2022)
Background and Aims We investigated the association between liver fibrosis scores and clinical outcomes in patients with COVID-19. Methods We performed a post-hoc analysis among patients with COVID-19 from the trial study Outcomes Related to COVID-19 treated with Hydroxychloroquine among Inpatients with symptomatic Disease (ORCHID) trial. The relationship between aspartate aminotransferase (AST) to platelet ratio index (APRI), non-alcoholic fatty liver disease fibrosis score (NFS), Fibrosis-4 index (FIB-4), and discharge and death during the 28-days of hospitalization was investigated. Results During the 28 days after randomization, 237 (80.6%) patients were discharged while 31 (10.5%) died among the 294 patients with COVID-19. The prevalence for advanced fibrosis was estimated to be 34, 21.8, and 37.8% for FIB-4 (>2.67), APRI (>1), and NFS (>0.676), respectively. In multivariate analysis, FIB-4 >2.67 [28-days discharge: hazard ratio (HR): 0.62; 95% CI: 0.46–0.84; 28-days mortality: HR: 5.13; 95% CI: 2.18–12.07], APRI >1 (28-days discharge: HR: 0.62; 95% CI: 0.44–0.87; 28-days mortality: HR: 2.85, 95% CI: 1.35–6.03), and NFS >0.676 (28-days discharge: HR: 0.5; 95% CI: 0.35–0.69; 28-days mortality: HR: 4.17; 95% CI: 1.62–10.72) was found to significantly reduce the discharge rate and increase the risk of death. Additionally, FIB-4, APRI, and NFS were found to have good predictive ability and calibration performance for 28-day death (C-index: 0.74 for FIB-4, 0.657 for APRI, and 0.745 for NFS) and discharge (C-index: 0.649 for FIB-4, 0.605 for APRI, and 0.685 for NFS). Conclusion In hospitalized patients with COVID-19, FIB-4, APRI, and NFS may be good predictors for death and discharge within 28 days. The link between liver fibrosis and the natural history of COVID-19 should be further investigated.